Extracellular Vesicles From Notch Activated Cardiac Mesenchymal Stem Cells Promote Myocyte Proliferation and Neovasculogenesis - Xuan, Wanling; Khan, Mahmood; Ashraf, Muhammad (Frontiers in Cell and Developmental Biology, 2020)
Cardiac mesenchymal stem cells (C-MSC) are a novel mesenchymal stem cell (MSC) subpopulation derived from cardiac tissue, which are reported to be responsible for cardiac regeneration. Notch signaling is believed to aid in cardiac repair following myocardial injury. In this study, we have investigated the role of extracellular vesicles (EV) from Notch1 engineered C-MSC on angiogenesis and cardiomyocyte (CM) proliferation in ischemic myocardium. C-MSC were isolated from Notch1flox mice (C-MSCFF). Notch1 gene deletion was accomplished by adenoviral vector mediated Cre recombination and Notch1 overexpression was achieved by overexpression of Notch1 intracellular domain (N1ICD). EV were isolated by using size exclusion column method. Proteomic composition of EV was carried out by Mass spectrometry. Mouse myocardial infarction (MI) model was generated by permanent LAD ligation. Intramyocardial transplantation of Notch1 knockout C-MSC (C-MSCNotch1 KO) did not have any effect on cardiac function and scar size. On the other hand, transplantation of N1ICD overexpressing C-MSC (C-MSCNICD) showed significant improvement in cardiac function and attenuation of fibrosis as compared to control (PBS) group and non-modified C-MSC groups. C-MSCNICD differentiated into smooth muscle cells and formed new vessels. Proteomics profiling identified several proteins, such as Lysyl oxidase homolog-2, biglycan as highly enriched proteins in EV-C-MSCN1ICD. Go term analysis indicated that EV-C-MSCN1ICD were enriched with bioactive factors, potent pro-repair proteins responsible for cell migration and proliferation. EV-C-MSC and EV-C-MSCN1ICD were strongly pro-angiogenic under both in vitro and in vivo conditions. EV-C-MSCN1ICD caused dense tube formation in vitro and increased neo-vasculogenesis in peri-infarct area in vivo. Furthermore, EV-C-MSCN1ICD attenuated endothelial cell and CM apoptosis under oxidative stress and ischemic injury. Similarly, EV-C-MSCFF and EV-C-MSCNICD treatment improved cardiac function and decreased fibrosis in mice post-MI. EV-C-MSCNICD were very effective in improving cardiac function and decreasing fibrosis. Notch1 signaling is strong stimulus for cardiac regeneration by C-MSC. EV secreted by Notch1 overexpressing C-MSC were highly effective in preventing cell death, promoting angiogenesis, CM proliferation and in restoring cardiac function post-MI. Overall, these results suggest that Notch1 overexpression may further enhance the effectiveness of EV secreted by C-MSC in cell-free therapy.